The lexical-semantic field of some color terms in the galician language - E A Platonova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2010)
The article covers the study of color-related vocabulary in one of the minor Romance languages of Spain, Galician. The study focuses on the six basic (main) color names: white, black, red, blue, green, yellow. The lexical-semantic fields of the main color terms are analyzed in the framework of synchronic and diachronic linguistics, allowing the researcher to isolate some special features of the functioning and usage of certain color terms in Galician, making a comparison to other languages that are nearly related to it.